Bianchi V I_0 Universe with Magnetized Strange Quark Matter in f(R, T) Theory - Can Aktaş; Sinem Kalkan (Journal of New Theory)
This study discusses f(R,T) theory, one of the alternative theories. It then studies magnetized strange quark matter in the universe model Bianchi V I0, homogeneous and anisotropic. Afterwards, it has determined whether the energy conditions are provided by using the deceleration parameter while obtaining the solutions. Moreover, the evolution of the cosmic universe is examined with the help of graphics and tables.